The Impact of Room Attendant’s Service Quality on Guest Satisfaction at BWP Hotel Batam - Fatimah, Zahara; Lubis, Arina Luthfini; Sitorus, Sri Wahyuningsih (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
The growth of the tourist industry need a variety of supporting aspects, one of which is hotel accommodation. BWP Panbil Batam is a four-star plus hotel with a premium concept that opened in 2016 in Batam City. BWP Panbil has numerous departments to assist operating activities, the most important of which is the housekeeping department, particularly in the room attendant position. BWP Panbil Batam continues to try to enhance services in order to maintain a positive image and ensure that visitors are content with what they pay for and what they receive. To clarify the topic matter or research findings, this study employs quantitative methods with a descriptive approach. Using the Slovin algorithm, the researchers collected a sample of 100 responses from customers who stayed at the BWP Panbil Batam Hotel between January and June 2022. Based on the partial test known as t-test, it is possible to infer that hypothesis H1 is accepted in this research and hypothesis null (H0) is rejected. The R2 value is 0.595, as determined by the determinant coefficient test findings. This suggests that service quality influences client satisfaction at the BWP Panbil Batam Hotel by 59.5%, with the remaining 40.5% impacted by other independent factors not investigated in this study.